2011
DOI: 10.1074/jbc.m110.181529
|View full text |Cite
|
Sign up to set email alerts
|

Activation Loop Phosphorylation of ERK3/ERK4 by Group I p21-activated Kinases (PAKs) Defines a Novel PAK-ERK3/4-MAPK-activated Protein Kinase 5 Signaling Pathway

Abstract: Classical mitogen-activated protein (MAP) kinases are activated by dual phosphorylation of the Thr-Xxx-Tyr motif in their activation loop, which is catalyzed by members of the MAP kinase kinase family. The atypical MAP kinases extracellular signal-regulated kinase 3 (ERK3) and ERK4 contain a single phospho-acceptor site in this segment and are not substrates of MAP kinase kinases. Previous studies have shown that ERK3 and ERK4 are phosphorylated on activation loop residue Ser-189/Ser-186, resulting in their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 31 publications
3
73
0
Order By: Relevance
“…Furthermore, we found that Rac1 can regulate FSP-1-induced MEK5/ERK5 phosphorylation and VSMC proliferation ( Figure 7G and 7H). Similar responses have been reported that Rac1 involved in regulating MAPK activation through p21-activated kinases 36 or JNK/AP1 pathway. 37 In contrast, FSP-1-stimulated Rac1 activation could not be inhibited by negative dominant MEK5, suggesting that Rac1 acts as an upstream of ERK5.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, we found that Rac1 can regulate FSP-1-induced MEK5/ERK5 phosphorylation and VSMC proliferation ( Figure 7G and 7H). Similar responses have been reported that Rac1 involved in regulating MAPK activation through p21-activated kinases 36 or JNK/AP1 pathway. 37 In contrast, FSP-1-stimulated Rac1 activation could not be inhibited by negative dominant MEK5, suggesting that Rac1 acts as an upstream of ERK5.…”
Section: Discussionsupporting
confidence: 62%
“…Some of the atypical MAPKs have to be phosphorylated on a single serine residue by IPAKs for elicitation [5]. Other representatives of atypical MAPKs, such as ERK7/8 gain their activity by intramolecular autophosphorylation on both phosphoacceptor sites of the TXY motif [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of protoplast and polyethylene glycol-mediated protoplast transformation were carried out as described by Anthony et al [20]. We used 5 μg plasmid DNAs to transform 2x10 5 protoplasts, and then cells were cultured for 16 h in dark at room temperature before harvesting. In case of myc-GOF-AtMKK co-transformation, 5:1 ratio was applied; 5 μg of AtMPK9-HA coding vector and 1 μg of different myc-GOF-MKK constructs.…”
Section: In Vitro Transcription and Cell-free Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK3 was recently shown to be activated by group I p21-activated kinases (PAKs) that include PAK1, PAK2, and PAK3 (29,30). Group I PAKs are important regulators for cell migration and invasion.…”
Section: Erk3 Interacts With and Phosphorylates Src-3 At S857 Althoumentioning
confidence: 99%